In vitro validation of chromogenic substrate assay for evaluation of surrogate FVIII-activity of emicizumab. Issue 222 (February 2023) - Yamaguchi, Tomoko; Shinozawa, Keiko; Nagatoishi, Satoru; Mitsuhashi, Ayano; Bingo, Masato; Inaba, Hiroshi; Amano, Kagehiro; Tsumoto, Kohei; Kinai, Ei
Abstract: [Introduction] Emicizumab, a bispecific antibody mimicking activated factor VIII (FVIII), is increasingly used in prophylaxis against bleeding in hemophilia A. Human factor-based chromogenic substrate assay (hCSA) shows concentration-dependency between emicizumab and reported FVIII activity. However, the assay measurement settings have not been optimized for emicizumab, and the reported FVIII activity cannot be directly referred as surrogate FVIII activity. [Materials and Methods] For in vitro validation of hCSA-reported surrogate FVIII activity, we compared the equation curves for emicizumab concentration with surrogate FVIII activity using spiked plasma in the thrombin generation assay (TGA), hCSA, and clot waveform analysis (CWA). Then, we generated conversion equations for hCSA-reported surrogate FVIII value to that of TGA. We also assessed the additive effect of rFVIII onto 340 nM (i.e., 50 μg/mL) emicizumab using the same assays. [Results] With 1:20 diluted plasma, halving hCSA-reported surrogate FVIII activity can be approximated to that in TGA triggered by the extrinsic pathway reagent (27.3 IU/dL vs. 13.9 IU/dL) under therapeutic emicizumab concentration. Both in TGA and hCSA, the additive effect of added FVIII on therapeutic emicizumab concentration (340 nM) was maintained at low levels of FVIII but gradually decreased at higher levels. [Conclusions] Surrogate FVIII activity can be estimated simply by halving hCSA-reported FVIII value, and the additive effect of FVIII on emicizumab diminishes at high concentrations. Based on our in vitro study, a clinical study is currently being conducted to compare individual variation of surrogate FVIII activity in hCSA and TGA.